2008
DOI: 10.1073/pnas.0805616105
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide expression profiling reveals distinct clusters of transcriptional regulation during bovine preimplantation development in vivo

Abstract: Bovine embryos can be generated by in vitro fertilization or somatic nuclear transfer; however, these differ from their in vivo counterparts in many aspects and exhibit a higher proportion of developmental abnormalities. Here, we determined for the first time the transcriptomes of bovine metaphase II oocytes and all stages of preimplantation embryos developing in vivo up to the blastocyst using the Affymetrix GeneChip Bovine Genome Array which examines approximately 23,000 transcripts. The data show that bovin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
113
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(140 citation statements)
references
References 52 publications
14
113
0
2
Order By: Relevance
“…Poly (A) C RNA was isolated using a Dynabeads mRNA DIRECT micro kit (610.21, Invitrogen Dynal AS) with some modifications to the manufacture's instructions as previously described (Kues et al 2008. Briefly, 40 ml of lysis-binding buffer (100 mM TrisHCl, pH 7.5, 500 mM LiCl, 10 mM EDTA, 1% lithium dodecyl sulphate (LiDS), 5 mM dithiothreitol) were pipetted into each sample tube, followed by addition of 1 pg rabbit globin mRNA (Bethesda Research Laboratories, Gaithersburg, MD, USA) as external standard.…”
Section: Mrna Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly (A) C RNA was isolated using a Dynabeads mRNA DIRECT micro kit (610.21, Invitrogen Dynal AS) with some modifications to the manufacture's instructions as previously described (Kues et al 2008. Briefly, 40 ml of lysis-binding buffer (100 mM TrisHCl, pH 7.5, 500 mM LiCl, 10 mM EDTA, 1% lithium dodecyl sulphate (LiDS), 5 mM dithiothreitol) were pipetted into each sample tube, followed by addition of 1 pg rabbit globin mRNA (Bethesda Research Laboratories, Gaithersburg, MD, USA) as external standard.…”
Section: Mrna Isolationmentioning
confidence: 99%
“…This highlights the importance of using alternative animal models to laboratory mice for investigations on humanrelated endocrine pathologies. Since Bos taurus is a good model species for early human embryo development (Ménézo & Hérubel 2002, Baumann et al 2007, Kues et al 2008, Velazquez 2008, bovine in vitro embryo production (IVP) could provide a good experimental model system for unravelling mechanisms involved in the putative impaired development of embryos exposed to high concentrations of IGF1. A cross-species microarray hybridisation study revealed that gene expression profiles in bovine and human blastocysts were to a large extent identical (Adjaye et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, detrimental effects on germ cells may become obvious in the following generation. After fusion of the gametes, a series of reprogramming events is activated, which includes DNA methylation, protamine exchange, histone marks, embryonic genome activation and degradation of maternal and paternal transcripts and proteins (Bermejo- Alvarez et al 2008, Kues et al 2008a. A well-orchestrated succession of these events is required to allow normal development, potentially making gametes and early embryos vulnerable to NPs, which may accumulate in the reproductive tract or which are intentionally added to spermatozoa in vitro (Bonde 2010, Ema et al 2010, Schrand et al 2010.…”
Section: Sperm Toxicity Of Aunpsmentioning
confidence: 99%
“…These factors are too often neglected, as the introduction of methodological artifacts is common for RNA abundance reports during prehatching development. For instance, through a retrospective data compatibility assessment performed using the published RNA abundance profiles produced by qRT-PCR of 15 candidate genes (Vigneault et al 2004, 2009, McGraw et al 2007) and a published microarray dataset aimed to describe the bovine prehatching development (Kues et al 2008), we observed important discrepancies in the relative transcript abundance patterns among immature oocyte, eight-cell embryo, and blastocyst for 80% of the candidates (12/15). Without the use of a way to account for the natural RNA abundance differences between the developmental stages during sample amplification, hybridization, and data normalization, it is challenging to determine whether methods could have introduced a bias that deeply influenced the downstream conclusions.…”
Section: Resultsmentioning
confidence: 99%